The PENERAPAN CUSTOMER RELATIONSHIP MANAGEMENT PADA PENJUALAN GAS MEDICAL DENGAN METODE EXTREME PROGRAMMING - Noer Azni Septiani (Politeknik Bisnis Indonesia, 2022)
The world is facing covid 19, countries are fighting against a virus that has been declared a global epidemic or pandemic by the World Health Organization. The need for medical gas during the Covid-19 pandemic is facing very high demand, both from hospitals and individuals. The problem with PT Gasindo Andalan Sukses is that the sales process is still carried out manually, marketing and offering products by visiting prospective customer locations so that it takes longer time and the success rate is erratic because there is still a price bargaining process. Based on these problems the author aims to create a web-based medical gas sales application at PT. Gasindo Andalan Success using customer relationship management (CRM) and Extreme Programming (XP) methods. The author hopes that it will be the right solution to make it easier for companies to market their products online to consumers. Another advantage is that companies can store data easily because of a computerized system.